CHILDBIRTH EXPERIENCE DURING THE COVID-19 PANDEMIC IN MATERNITY CARE INSTITUTIONS IN LATVIA - Kovale, Sabine; Teraudkalna, Madara; Vasioleka, Beate; Rasnaca, Kristine (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The COVID-19 pandemic has had a major impact on people’s lives worldwide, causing stress and anxiety for many people, including pregnant women. In addition do not knowing the implications of the new disease, pregnant women may also be negatively impacted by public health actions, such as limitations for accompanying persons to participate in childbirth and overall social distancing. The main objective of the research is to compare childbirth among women who gave birth during the COVID-19 pandemic with a control group. The data was collected using a questionnaire for Assessing the Childbirth Experience. 537 women who gave birth in 2019 and 2020 were included in the research and divided into two groups based on whether they gave birth before or after the state of emergency was declared in Latvia on March 12, 2020. The data was analysed using the IBM SPSS statistics program. The results showed that the childbirth experience for women giving birth without an accompanying person was statistically inferior on several accounts (process control, level of fear, breastfeeding support, etc.) than for women who had an accompanying person participating. In the research group there were proportionally more such women than in the control group, showing that COVID-19 has negatively impacted childbirth experience for many women.